TREATMENT OF PREGNANT WOMEN WITH CONSTIPATION IN PMB YUNI WIDARYANTI, AMD. KEB SEMANDING VILLAGE, MAYANGAN JOMBANG - Dian Puspita Yani; Suyati Suyati; Arifa Retnowuni; Ashila Muhajir (International Journal of Social Science, 2021)
Constipation is actually mostly physiological, but if there is no assistance through midwifery care, it is possible that pathological conditions will occur. The purpose of this midwifery care is to provide midwifery care in accordance with the 7 steps of Varney's midwifery care. The method used in conducting midwifery care for Mrs. This “P” is Varney's 7 steps of midwifery care. Includes assessment of basic data, interpretation of basic data, identification of diagnoses and potential problems, determining immediate needs, developing a plan of care, implementation and evaluation that has been carried out in stages and procedures. The results to Mrs. "P" in the basic data assessment, subjective data was found with complaints of difficulty in defecating for 4 days and objective data. The plan of care, implemented, and than final evaluation was obtained by Mrs. “P” constipation was resolved on day 2 of home visits by counseling and consuming apple juice taken 1 hour before bedtime. At the next visit defecation was smooth. The conclusion that can be drawn from this midwifery care is the implementation process of fulfilling nutrition that is rich in fiber and adequate fluid intake. Mrs “P” defecated smoothly according to plan with a final evaluation after 4 days of visiting the client's.